Equity Portfolio Optimization With Gold - Izabela Pruchnicka-Grabias (Problemy Zarządzania, 2021)
Purpose: The aim of the paper is to check if gold helps improve stock portfolio characteristics understood in the sense of the Markowitz model. If so, what are optimal shares of stocks and gold to minimize variance? Design/methodology/approach: The investment portfolio optimization procedure in the Markovitz environment is made. The study is devoted to investments made by Polish investors, that is stocks are reflected by the WIG index from the Warsaw Stock Exchange. The analysis is conducted in different periods of time in 2006–2019 covering bull and bear markets of gold. Findings: It is shown that gold can be used as a hedge asset; however, exact conclusions depend on the market situation. Including gold in the stock portfolio increases the portfolio rate of return and at the same time decreases risk measured with variance, however only during the bull market of gold. During the bear market, gold helps minimize risk but at the same time it lowers the portfolio rate of return compared to stocks-only portfolio. Besides, it turns out that during the bull market of gold, both skewness and kurtosis of the portfolio are more advantageous for an optimal portfolio covering both stocks and gold than for the stock one. Research limitations/implications: An important assumption of the study is in what way investments in gold are made. Here, they are made by the use of spot gold prices and they are recalculated into Polish zlotys in order to check the Polish investor perspective. In reality, it is not easy to invest directly in big amounts of gold, although in the literature spot gold prices are used for such research. Originality/value: The research contributes to the existing international literature on using gold in stock portfolio management by analyzing the problem from the point of view of a Polish investor. Originality/value: Original work.